Corrigendum to “Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol” [Biores. Technol. 390 (2023) 129855] - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2026)

Ultrasound-activated azido-sulfonamide prodrug nanoparticle with antibacterial peptide targeting for selective bacterial infection therapy - Jiali Sun; Jiahui Pan; Xitong Ren; Zecheng Chang; Wenfang Wang; Guoqing Wang; Jianting Xu; Jianshi Du; Haochen Yao (Chemical Engineering Journal, 2026)

Insight into poplar fractionation enhancement via an eco-manufacturing process using sulfonated magnetic polystyrene solid acid and biphasic solvent - Haochen Du; Cuiyi Liang; Shijun Liu; Xuesong Tan; Yang Chen; Shiyou Xing; Yu Zhang; Wei Liu; Wen Wang; Xin Shi; Zhongming Wang; Wei Qi (Chemical Engineering Journal, 2026)

Mobile MAX-DOAS measurements and source analysis of NO2, HCHO, and HONO during the Chengdu 2023 FISU world university games - Qijin Zhang; Chengzhi Xing; Miao Feng; Yinshuo Ding; Zhongmou Sun; Yikai Li; Haochen Peng; Wei Tan; Zhiguo Zhang; Tianjun Du; Cheng Liu (Journal of Environmental Sciences, 2026)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

Effects of warming and phosphorus on the stoichiometry of native and invasive plant and their rhizosphere soil - Miaomiao Cui; Jie Dong; Bin Yang; Haochen Yu; Xue Fan; Zhaoqi Zhu; Guangqian Ren; Daolin Du (Flora, 2025)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

Arbuscular mycorrhizal fungi enhance glyphosate resistance in an invasive weed: Implications for eco-environmental risks - Shanshan Qi; Daiyi Chen; Mengting Yan; Zhiyun Huang; Haochen Yu; Guangqian Ren; Hu'anhe Xiong; Wei Fu; Biying Zhao; Zhicong Dai; Daolin Du; Torsten Thomas (Applied Soil Ecology, 2025)

Advances of Complex Marine Environmental Influences on Underwater Vehicles - Sen Zhao; Haibao Hu; Abdellatif Ouahsine; Haochen Lu; Zhuoyue Li; Zhiming Yuan; Peng Du (Journal of Marine Science and Engineering, 2025)
Underwater vehicles serve as critical assets for global ocean exploration and naval capability enhancement. The marine environment exhibits intricate hydrodynamic phenomena that significantly threaten underwater vehicle navigation safety, particularly in four prevalent complex conditions: surface waves, oceanic currents, stratified fluids, and internal waves. This comprehensive review systematically examines the impacts of these four marine environments on underwater vehicles through critical analysis and synthesis of contemporary advances in theoretical frameworks, experimental methodologies, and numerical simulation approaches. The identified influences are categorized into five primary aspects: hydrodynamic characteristics, dynamic response patterns, load distribution mechanisms, navigation trajectory optimization, and stealth performance. Particular emphasis is placed on internal wave interactions, with rigorous analysis derived from experimental investigations and numerical modeling of internal wave dynamics and their coupling effects with underwater vehicles. In addition, this review points out and analyzes the shortcomings of the current research in various aspects and puts forward some thoughts and suggestions for future research directions that are worth further exploration, including enriching the research objects, upgrading the experimental techniques, and introducing artificial intelligence methods.

Light-enhanced ion transport and fouling resistance properties of metal/semiconductor heterojunction nanochannel membranes for osmotic energy recovery in real-world conditions - Haochen Lu; Jin Wang; Derong Zhang; Tongxin Liao; Shangzhen Li; Lei Lei; Zhiyan Liu; Bingjie Du; Xudong Wang; Lei Wang (Water Research, 2025)

Global Environmental Change Shifts Ecological Stoichiometry Coupling Between Plant and Soil in Early-Stage Invasions - Guangqian Ren; Miaomiao Cui; Haochen Yu; Xue Fan; Zhaoqi Zhu; Haiyan Zhang; Zhicong Dai; Jianfan Sun; Bin Yang; Daolin Du (Journal of Soil Science and Plant Nutrition, 2024)

Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2023)

Recognition of airfoil wake structure based on deep learning - Haibao Hu; Xiangbo Du; Haochen Lu; Xiaopeng Chen; Peng Du (Ocean Engineering, 2023)

Mitogenome analysis reveals predominantly ancient Yellow River origin of population inhabiting Datong agro-pastoral ecotone along Great Wall - Yuqing Yan; Panxin Du; Jihong Zhang; Ruilan Li; Haoquan Bao; Qingli Fang; Ye Gao; Hailiang Meng; Yiran Xu; Haochen Shi; Hailong Yan; Xin Chang; et al. (Molecular Genetics and Genomics, 2023)